(untitled) (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
Study This aim For know influence workplace diversity , discipline work , compensation , and loyalty to performance employees of CV. Saprotan Utama Semarang. Research This use method quantitative with type study survey . Taking sample sample done with use method probability sampling with amount respondents studied​ as many as 181 performances employees . The data collection process is carried out with method spread questionnaire in a way directly on performance employees of CV. Saprotan Utama Semarang. Research This using IBM SPSS 25 software with regression testing multiple as method testing hypothesis Results of analysis and discussion show variables influential positive and significant between workplace diversity, discipline work , compensation , and loyalty to performance employees . Analysis results show that workplace diversity variable value significance of 0.000 has an effect positive significant to performance employees , discipline Work mark significance 0.44 has an effect positive significant to performance employees , Compensation mark significance 0.52 not effect positive significant to performance employee , Loyalty mark significance of 0.001 has an effect positive significant to performance employee